Translation and validity of Acquired Capability for Suicide Scale Fearlessness About Death in Peruvian adults - Baños-Chaparro, Jonatan (2023)
The Interpersonal Theory of Suicide proposes that the presence of suicidal behavior is explained by the suicidal desire and capacity acquired in the individual. Fearlessness about death is a dimension of said capacity and is a potential risk factor for suicide. The objective was to realize Spanish translation and validation of the Acquired Capability for Suicide Scale Fearlessness About Death in Peruvian adults from the general population. The methodology of the study was cross-sectional study of quantitative and instrumental approach. A total of 929 Peruvian adults who responded the Acquired Capability for Suicide Scale - Fearlessness About Death (ACSS-FAD) participated. The reverse translation method was used for the English to Spanish version. Analyses were performed as from classical test theory and item response theory. The results indicate that the ACSS-FAD evidences a unidimensional structure (CFI = .99, RMSEA = .07 [90 % CI: .06 – .09], SRMR = .03], adequate reliability (α = .84 and H = .86), invariance and differential item functioning according to sex. In addition, all items discriminated adequately, with items 5 and 4 being more accurate in measuring fearlessness about death. In conclusion, the Spanish version of the ACSS-FAD presents sources of evidence of validity based on content, internal structure, reliability, invariance and item responses. Its use is recommended for the interpretation and inference of its scores in the assessment of stigma towards the suicide in the general adult Peruvian population.